Genomic New Insights Into Emergence and Clinical Therapy of Multidrug-Resistant Klebsiella pneumoniae in Infected Pancreatic Necrosis - Hao, Haibin; Liu, Yang; Cao, Jin; Gao, Kun; Lu, Yingying; Wang, Weiping; Wang, Peng; Lu, Sida; Hu, Long; Tong, Zhihui; Li, Weiqin (Frontiers in Microbiology, 2021)
Infected pancreatic necrosis (IPN) is the key risk factor in the progression of severe acute pancreatitis, and use of antibiotics is one of the main clinical actions. However, early prophylactic or unreasonable use of antibiotics promotes drug resistance in bacteria and also delays optimum treatment. To explore genomic evidence of rational antibiotic use in intensive care units, we isolated Klebsiella pneumoniae from IPN samples, which showed the highest positive-culture rate in 758 patients. Based on whole-genome sequencing from eight strains, 42 antibiotic-resistant genes were identified in the chromatin and 27 in the plasmid, which included classic resistance-mechanism factors such as β-lactamases (16.67% [7/42] in the chromatin and 25.93% [7/27] in the plasmid). The K. pneumoniae isolates were identified to be resistant to multiple antibiotics used in clinics. In vivo and in vitro, ceftazidime-avibactam (CZA) plus aztreonam (ATM) (2.5:1) showed more significant antibacterial effectiveness than CZA alone. The isolated K. pneumoniae were of three different types according to the resistance phenotypes for CZA and ATM. Those co-harboring blaNDM-5, blaCTX-M-15, blaOXA-1, and blaSHV-187 showed higher resistance to CAZ than blaNDM-5. Those co-harboring blaCTX-M-65, blaSHV-182, and blaTEM-181 were significantly less resistant to β-lactam than to other extended-spectrum β-lactamases. However, β-lactamases were inhibited by avibactam (AVI), except for NDM-5. ATM plus AVI showed a significant inhibitory effect on K. pneumoniae, and the minimum dosage of ATM was < 1 mg/L. In conclusion, we propose that ATM plus AVI could be a major therapy for complex infectious diseases caused by multidrug-resistant K. pneumoniae.